The effects of P. aeruginosa ATCC 9027 and NTA on phytoextraction of Cd by ramie (Boehmeria nivea (L.) Gaud). Issue 83 (9th September 2015) - Xie, Jieli; Liu, Yunguo; Zeng, Guangming; Liu, Huan; Zheng, Bohong; Tang, Hui; Xu, Weihua; Sun, Zhichao; Tan, Xiaofei; Nie, Jian; Jiang, Zhengjiang; Gan, Chao; et al.
<x xml:space="preserve">Abstract</x> The effects of Pseudomonas aeruginosa ATCC 9027 and nitrilotriacetic acid (NTA) on Cd phytoextraction from contaminated soil by Boehmeria nivea (L.) Gaud was investigated.